Prevalence of burnout among urologist and its risk factors in Indonesia - Reginald Rustandi; Fakhri Rahman; Raga Manduaru; Chaidir Arif Mochtar (African Journal of Urology, 2024)
Abstract Objective To evaluate burnout syndrome among Indonesian urologists by describing its prevalence and risk factors. Materials and methods This is a cross-sectional study conducted from February to April 2020. A validated Indonesian version of the Maslach Burnout Inventory that consists of 22 questions addressing emotional exhaustion, depersonalization, and personal achievement was utilized. The questionnaire was constructed using Google Forms (Google, Inc.) and was distributed via e-mail and WhatsApp Messenger (Facebook, Inc.). Burnout was defined as either high score on emotional exhaustion, or high score on depersonalization, or low score on personal achievement. Several variables were analyzed as risk factors to burnout using multivariate analysis. All statistical analyses were carried out using Statistical Software for Social Science (SPSS) version 23. Results From 486 eligible members of IUA, 184 (37%) respondents completed the questionnaire. Burnout syndrome was detected in 43 respondents (23.4%). From the results, most of the respondents have low EE (54.9%), low DP (77.7%), and moderate PA (45.7%). Bivariate analysis showed that age of less than 44 years old and being single were associated with increased risk of burnout with OR 2.2 (1.0–5.1, 95% CI, p-value 0.04) while being married decreases risk of burnout with OR 0.2 (0.1–0.8, 95% CI, p-value < 0.01). Lower work load in COVID-19–19 era was related to protective results with OR 0.4 (0.2–0.9, 95% CI, p-value 0.03). Multivariate analysis showed that being married decreases risk of burnout with OR 0.3 (0.1–0.9, 95% CI, p-value 0.04). Multivariate analysis showed that being married was the only significantly protective factor from burnout. Conclusion Burnout syndrome among majority of urologists in Indonesia has a moderate degree of burnout, with being married the only significant factor influencing burnout in this study.